Praktik Manajemen Humas dalam Meningkatkan Citra Lembaga melalui Pemberitaan di LPP RRI Takengon - Farid Fauzi (Al-DYAS, 2026)
Field practice is a form of applied learning aimed at enhancing students’ competencies through the application of theory in the workplace. This article aimed to describe the implementation of public relations management by students of the Islamic Education Management Study Program at IAIN Takengon during their field practice at Lembaga Penyiaran Publik RRI Takengon. This study employed a descriptive qualitative approach, with data collected through observation, direct participation, interviews, and documentation during the field practice. The findings showed that public relations management at LPP RRI Takengon had implemented the functions of planning, organizing, implementation, and supervision in managing news reporting. The students were involved in preparing news agendas, conducting news coverage, writing news reports, documentation, and publication through broadcast and digital media. These activities provided practical experience in developing competencies in communication, teamwork, news writing, digital media management, and workplace professionalism. This practice also strengthened students’ understanding of the strategic role of public relations in establishing public communication and enhancing the institution’s image through accurate, objective, and responsible news reporting. These findings confirm that field practice at a broadcasting institution can serve as an effective means of integrating the managerial, communication, and professional competencies of Islamic Education Management students.